G-CuP: the effect of a forced oral glucose intake on alcohol craving and mesolimbic cue reactivity in alcohol dependence-study protocol of a randomized, double-blind, placebo-controlled crossover study - Wetzel, Lea; Pourbaix, Madeleine; Riegler, Alisa; Pfeifer, Anna-Maria; Reinhard, Iris; Hoffmann, Sabine; Vollstädt-Klein, Sabine; Kiefer, Falk; Sommer, Wolfgang H.; Bumb, Jan Malte; Bach, Patrick; Koopmann, Anne (Trials, 2022)
Background Multiple studies indicate that a lower plasma level of the acetylated form of the appetite-regulating hormone ghrelin and higher plasma levels of insulin lead to a reduction in subjective alcohol craving and a reduced mesolimbic cue reactivity in functional magnetic resonance imaging (fMRI) when being exposed to alcohol-associated stimuli. The ghrelin level can physiologically be reduced by the induction of stomach distension and the ingestion of glucose or lipids. Methods A total of 108 alcohol-dependent patients aged between 18 and 65 years are examined in the randomized, double-blind, placebo-controlled crossover study. After collecting demographic and psychometric data, participants take part in an alcohol exposure session. Afterwards, the participants go through the intervention condition (oral glucose intake) and the control condition (placebo intake) in a randomized order on two examination days. Blood samples are taken repeatedly (every 10 min) during the study course on both measuring days to determine changes in acetylated and total ghrelin and insulin plasma levels. In parallel, subjective alcohol craving after the glucose or placebo intake as the primary outcome is assessed using the Alcohol Urge Questionnaire (AUQ) and a visual analog scale (VAS). To examine the mesolimbic cue reactivity as the secondary outcome, a fMRI measurement is conducted while being exposed to alcohol-related stimuli. Appropriate statistical analysis will be used for the evaluation of the outcomes. Discussion If successful, the results of this study could offer alcohol-dependent patients a new potential option for acute short-term reduction of alcohol craving and thus prevent relapses and prolong periods of abstinence in the long term.